Federalism Practice in Nepal: Does it Move in the Expected Course? - Acharya, Keshav K. (Dhaulagiri Journal of Sociology and Anthropology, 2021)
This study examines how far Nepal's current practice of federalism has progressed toward people's aspirations, based on power separation, public trust, power equalization, and intergovernmental relationships. Primary data was collected on purposively 72 key informant interviews, which were then triangulated by the KII response. Finding demonstrates that functions and authorities were devolved in accordance with the principle of separation of powers at all three levels of government. However, the constitutional provisions were completely disregarded, and power was centralized by an unholy alliance of political leadership and bureaucracy. Second, people expected the democratic government to take a welfare approach to ensure greater pluralism and alliances, but special interests of politicians for their election constituencies, as well as identity-based issues, caused havoc in the effective operation of federalism. Third, the provision of three tiers of power-sharing mechanisms was based on coexistence, cooperation, and coordination. However, the federal government appears hesitant to support sub-national governments due to the centralized mindset of bureaucrats and politicians. Fourth, the constitution has focused on intergovernmental relations, but such relationships fail due to imbalances in vertical and horizontal relationships, fiscal dependency, and the bureaucracy's power-seeking attitude. In the end, two key questions for the discussions are raised. First, the institutionalization of accountability at the local level is it a true commitment, or is it merely an ivory tower? Second, the provision of autonomy has been used as a means of transformation or simply as a bargaining tool at the local level?